Health status of the Ex-British Nepalese army men who underwent General Health check-up in TUTH - Shakya, Y M (Journal of Institute of Medicine Nepal, 2007)
Background: Most Nepalese without major recognizable medical symptoms in their lives, do not feel the need for a whole body checkup. If we timely evaluate their health, we can prevent ongoing major complications and even sudden unexplained death. If we do regular good health checkups every 1- 2 year generally after 35 yrs. of age,. we can detect diseases in its very early stage. This simple measure help to prevent major serious complications. Methods: The total number of candidates between age groups of 33-46 years ,during the 1 August 2004 to 30 July 2005 was 100 Nepalese Ex-British army men. They were presenting to. IOM, TUTH General health checkup department with the detail evaluations of their clinical histories, signs and all basic investigations without meat diet 18 hours before were done. All candidates came in fasting at 9 AM to the department for investigation of, total Hb, Sugar, Urea, Creatinine, SGPT, Lipid profile, Uric Acid, VDRL, Urine R/E, Stool R/E, Blood grouping, E.C.G., X-ray chest, USG of Abdomen, HBsAg, HIV, etc. Results: Amongst the 100 Nepalese Ex-British army men between 33 to 46 yrs. of age. They thought that they were physically and mentally fit for the work without any ongoing major problems. On routine whole body examination: 22% of the candidates were diagnosed with hypertension, which they did not know before evaluation. Similarly 74% of candidates had high BMI ranging from 25-29.9%. Most of them were unaware of increased body weight. There was a correlation between high BMI and hypertension. The higher the BMI, higher was the Blood Pressure 66.66%. Similarly lower the BMI was lesser the Blood Pressure 7.69%. 18% of them were detected with high Triglyceride level (TG). 30% had raised Uric Acid level. 19 % of them had fatty liver. A high BMI is related to rise in TG level. i.e.11.54% among normal BMI and 66.67% in high BMI cases. Fatty liver was 11.53 % among non-Alcohol and 21.62% among alcohol using groups. Raised TG level from 11.53% among non Alcohol to 17.53% among Alcohol group. Use of Alcohol was not related to raised BMI. Similarly with Uric Acid also, not much difference was detected with non-alcohol group. Among Alcohol taking group, 21.62% had fatty liver and slight rise of TG 17.53%. Conclusion: The casual whole body checkup showed very significant and alarming findings. If they hadn't come for whole body checkup in order to work abroad as guards, they probably might have stayed at home with all the correctable problems and could have developed any complications in near future. The data collection showed a clear relationship between high BMI and High Blood Pressure, high Triglyceride and Fatty liver. If we are able to maintain our standard body weight, then one might have very good robust health. A alcohol intake showed certain percentage of Fatty liver and high TG. One must not take more than standard amount of alcohol in order to maintain normal BMI & BP. Journal of Institute of Medicine Vol.28(1) 2006